การจัดการความเสี่ยงด้านการเงินของกลุ่มสาขาวิชาวิทยาศาสตร์และเทคโนโลยี มหาวิทยาลัยเชียงใหม่ - สายฝน วงค์สุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objectives of this study, Financial Risk Management of Group of Science and Technology Faculty, Chiang Mai University are to 1) study Financial Risk of Group of Science and Technology Faculty, Chiang Mai University and 2) evaluate Financial Risk factors of Group of Science and Technology Faculty, Chiang Mai University. There are 46 people of the sample group in this study. The questionnaires showing the sample group’s opinions towards Financial Risk level of Group of Science and Technology Faculty, Chiang Mai University are used as data collecting instrument, including other factors affecting the financial risk management and data gathered analysis such as frequency, percentage, average standard deviation, simple correlation, and relation. The study is inferred that 1. Financial Risk level of Group of Science and Technology Faculty, Chiang Mai University is divided into 3 level The overall risk level is in the low level whose average is equal to 10.47 showing that the risk is not too excessive to control. The tactic risk, 6 tactics, found that they mostly are in the low level. The issue risk, 14 issues, found that they mostly are in the low level. 2. The overall of Financial Risk factors of Group of Science and Technology Faculty, Chiang Mai University is in the medium level with the total average around 3.11 and standard deviation around 0.50. The study can be concluded that Overall internal Financial Risk of Group of Science and Technology Faculty, Chiang Mai University is in the medium level with total average around 3.24 Overall external Financial Risk of Group of Science and Technology Faculty, Chiang Mai University is in the medium level with total average around 2.97 3. The result of the hypothesis The 1st hypothesis Financial Risk of Group of Science and Technology Faculty, Chiang Mai University found that Sig. (2-tailed) is more than 0.05. It means accepting the main hypothesis (H0), the financial risk management is in the high level. The2nd hypothesis Financial Risk factors of Group of Science and Technology Faculty, Chiang Mai University found that most of them have nothing related to one another. It means that financial risk do not affect the process to achieve the goal set by the organization. Suggestions 1. Managing Director is supposed to know and understand well in the policy setting and financial planning, including strictly controlling the budget along with the plan already set. So the organization has no or less risk. 2. Managing Director has to analyze and follow up the result of the project or other activities in order to keep it as planned and achieve the objectives set. This reduces the possible risk. 3. Authorities, officers, or operators are supposed to know and understand in financial risk management to prevent the possible risk. 4. Managing Director is supposed to set the strategic plan in advance and promote it to the officers related for understanding the organizer’s policy. 5. Financial risk management needs a continuous process. Following the result is considered as an important matter as well. Due to the new possible risk that keeps occurring, so the managing director and everyone who has related to, have to manage the risk of the organization an also know how to fix it.